Curriculum standardization, stratification, and students' STEM-related occupational expectations: Evidence from PISA 2006. (2015) - Han, Seong Won
Highlights: This paper examines cross-national differences in STEM occupational expectations. The study focuses on features of national education systems. Associations between education system and expectation differ across STEM fields. Associations between education system and expectation differ by gender. Associations between education system and expectation differ across student ability. Abstract: This paper uses data from the Program for International Student Assessment (PISA) 2006 to examine the associations between characteristics of national education systems (the standardization of curriculum, the number of school types available to 15-year-old students, and early tracking) and students' STEM occupational expectations. Results show that the associations between characteristics of national education systems and students' STEM occupational expectations differ by gender as well as across STEM subfields and academic performance levels. Students' computing and engineering occupational expectations are not associated with the characteristics of secondary education. The negative association between a standardized education system and students' health service occupational expectations is stronger for students at the bottom of the performance distribution than students at the top.